Gereja Ramah Disabilitas Sebagai Upaya Pelaksanaan Tri Tugas Gereja di GKPI Labuhan Batu - Daud Marsahata Simamora; Arip Surpi Sitompul; Rencan Carisma Marbun (Pusat Riset dan Inovasi Nasional, 2025)
A disability-friendly church is a concrete manifestation of the Christian faith's call to live out God's love in a tangible way in the lives of its congregation. The presence of people with disabilities in society and within church communities is often viewed as a neglected group, both in terms of physical accessibility, opportunities for participation, and involvement in ministry. However, theologically,people with disabilities are also God's creations, possessing the same dignity as other members of the congregation and deserving of equal space in church life. A disability-friendly church means a church that not only provides physical facilities but also fosters an attitude of acceptance, appreciation, and empowerment for people with disabilities so they can contribute to worship, ministry, and congregational life. This study aims to determine the extent of the efforts of the Indonesian Protestant Christian Church (GKPI)in Labuhanbatu, both in the Labuhanbatu Induk and Labuhanbatu Utara regions, in realizing a disability-friendly church as part of the Church's Three Tasks: Marturia (witness), Koinonia (fellowship), and Diakonia (loving service). The Three Tasks of the Church serve as an important benchmark for assessing the church's success in presenting God's love within the congregation, particularly to vulnerable groups such as people with disabilities. The research method used was qualitative with a descriptive approach. Thisapproach was chosen because it allowed researchers to understand the experiences, perceptions, and meanings of the participants in depth and context. Data collection techniques included field observation, in-depth interviews, and documentation.Eight informants participated in the research: two people wvith disabilities, two family members of people with disabilities, three church ministers, and one synod leader.